2020
DOI: 10.1177/0391398820917150
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic effects of oXiris haemofilter in septic shock patients requiring renal support: A single-centre experience

Abstract: Excessive pro-inflammatory and anti-inflammatory cytokines are mediators for haemodynamic alterations, metabolic acidosis, and multi-organ failure in sepsis. Recently, oXiris® haemofilter (Baxter, IL, USA) has been introduced as a novel haemofilter to mitigate inflammatory response during sepsis-associated acute kidney injury requiring renal replacement therapy. In the present case series, the researchers retrospectively reviewed critically ill patients with septic shock with the use of at least one oXiris hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
3
19
1
1
Order By: Relevance
“…Unfortunately, the lack of direct cytokine measurement and clearance calculation in both groups [10], no definitive conclusion can be made regarding that specific issue. Otherwise, in line with previous findings, reduction in SOFA scores may be linked to restoration of hemodynamic stability and increased oxygenation [17, 18].…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, the lack of direct cytokine measurement and clearance calculation in both groups [10], no definitive conclusion can be made regarding that specific issue. Otherwise, in line with previous findings, reduction in SOFA scores may be linked to restoration of hemodynamic stability and increased oxygenation [17, 18].…”
Section: Discussionsupporting
confidence: 90%
“…Another retrospective study in two French centres also demonstrated the benefit of oXiris membrane in haemodynamics, especially in abdominal septic patients or gram-negative bacilli (GNB) infection subgroup [27 ▪▪ ]. The haemodynamic improvement was also showed in one retrospective study from Thailand when patients were initiated oXiris treatment within 24 h of ICU admission, which indicated an earlier use having better hemodynamic effects [28].…”
Section: In-vivo Studymentioning
confidence: 88%
“…Additional (10-fold) higher amount of immobilised heparin e ciently reduces thrombogenicity [39]. It has shown a superb capacity to adsorb cytokines and endotoxins [40] control abnormal levels of systemic cytokines [41] and improve haemodynamic parameters [42,43]. To this end, our COVID-19 treatment bundle is based on the use of oXiris® blood puri cation to counter the multidimensional in ammatory attack on the body triggered by the SARS-CoV-2 virus.…”
Section: Discussionmentioning
confidence: 99%